(untitled) (Revista Peruana de Investigación Educativa, 2026)
This study aims to identify the role of low-cost private schools in school segregation by socioeconomic status in Lima. To this end, it analyzes microdata from the 4th-grade Primary level of the 2018 Student Census Assessment (ECE) conducted by the Ministry of Education, using Hutchens’ square root index. The final sample consisted of 113,233 students enrolled in 3,859 schools across 41 districts of the capital city. The results show that low-cost private schools are increasing overall segregation for both lower-income and higher-income students. However, the reality of low-cost schools varies significantly by district, highlighting the multidimensional nature of the issue and the importance of a local perspective for its understanding. Thus, the study provides evidence of the role played by low-cost private schools in school segregation, which affects the educational opportunities of children from low-income families in Metropolitan Lima. While these schools offer an alternative to public schools, it is necessary to address challenges related to affordability, quality, and regulation in order to maximize their impact on educational access and equity.